2020
DOI: 10.1007/s40747-020-00152-5
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy plant project selection with AHP decision-making method based on hesitant fuzzy linguistic evaluation

Abstract: Increased energy demand is expected to be met by reliable and continuous energy sources. Renewable energy which is obtained from nature and can continuously reload itself from natural sources is a new generation energy type. The sun, which is the main source of renewable energies and produces heat and electricity by direct and indirect methods, is an important renewable energy source. The installation of solar energy systems takes place under the basic technical, economic and political factors. Alternative sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There is currently a consensus that the business site selection problem is a Multi-Criteria Decision-Making problem (MCDM). Many examples can be found that use this approach to tackle the problem: the selection of a shopping center in Turkey [38], the selection of warehouses for agricultural products [39], the location of gas stations [19,40], the opening of a new supermarket in Spain [41], the selection of Surface Water Treatment [42] or solar energy plants [43], among many others.…”
Section: Related Literaturementioning
confidence: 99%
“…There is currently a consensus that the business site selection problem is a Multi-Criteria Decision-Making problem (MCDM). Many examples can be found that use this approach to tackle the problem: the selection of a shopping center in Turkey [38], the selection of warehouses for agricultural products [39], the location of gas stations [19,40], the opening of a new supermarket in Spain [41], the selection of Surface Water Treatment [42] or solar energy plants [43], among many others.…”
Section: Related Literaturementioning
confidence: 99%
“…Its mathematical simplicity and ease of use compared to other MCDM methods have established its popularity among researchers [70,83]. Because of its mathematical simplicity and ease of use, the technique has been successfully integrated with other MCDM methods [61,[84][85][86][87].…”
Section: Fuzzy Topsismentioning
confidence: 99%
“…The main purpose of entropy measures is to explain uncertainty degree. In recent years, numerous studies have integrated the entropy with various fuzzy sets types, such as; Burillo and Bustince [4], Coban [9], Joshi and Kumar [21], Yari et al [38,39], Szmidt and Kacprzyk [26], Farnoosh et al [14], Ye [40], Hung and Yang [18], Rahimi and Kumar [28], Rahimi et al [29], Wei et al [34], Zeng and Li [46], Szmidt and Kacprzyk [27], Ye [41], and Zhang et al [47]. Burillo and Bustince [4] have defined the interval-valued fuzzy sets and IFSs, and introduced the distance measure between IFSs using the entropy measures.…”
Section: Introductionmentioning
confidence: 99%